The Effect of Intellectual Intelligence, Emotional Intelligence and Communication on the Performance of Village Officials in Somagede District - Fendy Ninggar Haryanto; Hermin Endratno; Wida Purwidianti; Meydy Fauziridwan (Trescode Green Organization, 2026)
This study focuses on factors that influence employee performance, which are considered important to ensure readiness in facing the dynamics of local village community services. This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and communication on the performance of village officials in Somagede sub-district. This study is a quantitative study using a saturated sampling method, in which the researcher made all village officials in Somagede sub-district as a research sample, totaling 100 respondents. Data were collected using a questionnaire and processed using SPSS analysis. The results of this study indicate that intellectual intelligence, emotional intelligence, and communication have a positive and significant effect on performance. This study provides implications for village officials to conduct regular training. In addition, it is hoped that it will create a conducive, collaborative, and mutually respectful work environment that can trigger improved performance.